Librarians as partners in research data service development at Griffith University. Issue 4 (1st September 2015) - Andrew Cox, Dr; Searle, Samantha; Wolski, Malcolm; Simons, Natasha; Richardson, Joanna
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to describe the evolution to date and future directions in research data policy, infrastructure, skills development and advisory services in an Australian university, with a focus on the role of librarians. Design/methodology/approach – The authors have been involved in the development of research data services at Griffith, and the case study presents observations and reflections arising from their first-hand experiences. Findings – Griffith University's organisational structure and "whole-of-enterprise" approach has facilitated service development to support research data. Fostering strong national partnerships has also accelerated development of institutional capability. Policies and strategies are supported by pragmatic best practice guidelines aimed directly at researchers. Iterative software development and a commitment to well-supported enterprise infrastructure enable the provision of a range of data management solutions. Training programs, repository support and data planning services are still relatively immature. Griffith recognises that information services staff (including librarians) will need more opportunities to develop knowledge and skills to support these services as they evolve. Originality/value – This case study provides examples of library-led and library-supported activities that could be used for comparative purposes by other libraries. At the same time, it provides a critical perspective by contrasting areas of good practice within the University with those of less satisfactory progress. While other institutions may have different constraints or opportunities, some of the major concepts within this paper may prove useful to advance the development of research data capability and capacity across the library profession.